Cuttlefish conservation: a global review of methods to ameliorate unwanted fishing mortality and other anthropogenic threats to sustainability. (24th November 2022) - Barrett, C J; Bensbai, J; Broadhurst, M K; Bustamante, P; Clark, R; Cooke, G M; Di Cosmo, A; Drerup, C; Escolar, O; Fernández-Álvarez, F A; Ganias, K; Hall, K C; et al.
Abstract: Cuttlefish are an important global fisheries resource, and their demand is placing increasing pressure on populations in many areas, necessitating conservation measures. We reviewed evidence from case studies spanning Europe, Africa, Asia, and Australia encompassing diverse intervention methods (fisheries closures, protected areas, habitat restoration, fishing-gear modifications, promoting egg survival, and restocking), and we also discuss the effects of pollution on cuttlefish. We conclude: (1) spatio-temporal closures need to encompass substantial portions of a species' range and protect at least one major part of their life cycle; (2) fishing-gear modifications have the potential to reduce unwanted cuttlefish capture, but more comprehensive trials are needed; (3) egg survival can be improved by diverting and salvaging from traps; (4) existing lab rearing and restocking may not produce financially viable results; and (5) fisheries management policies should be regularly reviewed in light of rapid changes in cuttlefish stock status. Further, citizen science can provide data to reduce uncertainty in empirical assessments. The information synthesized in this review will guide managers and stakeholders to implement regulations and conservation initiatives that increase the productivity and sustainability of fisheries interacting with cuttlefish, and highlights gaps in knowledge that need to be addressed.